BIOGEOGRAPHY OF THE SPECIES OF THE EREMURUS L. SPECIES INCLUDED IN THE RED BOOK, THE SIGNIFICANCE IN THE NATIONAL ECONOMY AND PROPAGATION METHODS - Ne’matova Mokhinur; Iskandarova Yulduzoy Nizamitdinovna; Shakhnoza Doniyorova; Mokhira Halkuzieva (Journals Park Publishing, 2023)
The article provides information on the importance of Eremurus L. species in the national economy and the biogeography of the species included in the Red Book.
Keywords: Eremurus, Altai, Olga, Regel, flower, root, seed, pollen.